(untitled) (Modern American Journal of Engineering, Technology, and Innovation, 2026)
This article examines how geodetic data and architectural design can be integrated to improve the energy performance of low-rise residential buildings in Fergana region. The relevance of the study is determined by the rapid growth of housing construction in the region, the hot and dry summer climate, winter heat demand, and the need to reduce energy consumption in the building sector. The study combines regional statistical information, climatic indicators, geodetic site analysis, and a comparative assessment of four design scenarios for a 120 m² model house. The analysis uses topographic data, slope and aspect information, solar exposure, prevailing wind direction, and drainage patterns as primary geodetic inputs for site-responsive architectural planning. Results show that the conventional reference house with an annual specific energy demand of 235 kWh/m²·year can be improved to 152 kWh/m²·year when geodetic site planning is integrated with energy-efficient architectural and constructive measures. This represents an estimated reduction of 35.3%, equivalent to 9,960 kWh/year and about 2.01 t/year of CO₂ emissions for the model house. The findings confirm that the integration of geodesy and architecture is not only a spatial and design issue, but also an effective pathway to energy saving, cost reduction, and improved thermal comfort in low-rise housing.